2019
DOI: 10.4103/jisp.jisp_207_18
|View full text |Cite
|
Sign up to set email alerts
|

Periodontically accelerated orthodontic tooth movement: A narrative review

Abstract: Adult orthodontics has gained widespread acceptance recently with the introduction of more esthetic options for the patient. The major deterrent that remains is the prolonged treatment time associated with comprehensive orthodontic treatment. The objective of this paper is to present a review of techniques, which could be employed by the orthodontist in conjunction with a periodontist to enhance the rate of orthodontic tooth movement. The biological rationale and clinical manipulation have been discussed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Various methods have been described in the literature for speeding up space closure. 11,26 However, only recently have attempts been made to combine the two methods and check for any synergistic effect the 27 The authors concluded that the combination was more effective than the application of each technique separately. A similar synergistic effect may be observed if MOPs are combined with any other technique.…”
Section: Discussionmentioning
confidence: 99%
“…Various methods have been described in the literature for speeding up space closure. 11,26 However, only recently have attempts been made to combine the two methods and check for any synergistic effect the 27 The authors concluded that the combination was more effective than the application of each technique separately. A similar synergistic effect may be observed if MOPs are combined with any other technique.…”
Section: Discussionmentioning
confidence: 99%
“…The advances in dentistry and malocclusion corrections for development of a healthy occlusion have led to an increased demand of orthodontic treatment. Malocclusion can vary depending on certain factors including the dental angle classification, skeletal classification and genetic factors [ 1 3 ]. Orthodontic movements vary depending on the degree of malocclusion, other biological factors such as age and suspected treatment planning [ 2 – 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The advances in dentistry and malocclusion corrections for development of a healthy occlusion have led to an increased demand of orthodontic treatment. Malocclusion can vary depending on certain factors including the dental angle classification, skeletal classification and genetic factors (1)(2)(3) .…”
Section: Introductionmentioning
confidence: 99%
“…Orthodontic movements vary depending on the degree of malocclusion, other biological factors such as age and suspected treatment planning (2)(3)(4)(5) .…”
Section: Introductionmentioning
confidence: 99%